Design and Fabrication of a Smart Waste Bin Using Arduino for Improved Hygiene and Waste Management - Tina Ishioma Francis-Akilaki; Raymond Alex Ekemube (Greenation International Journal of Engineering Science, 2026)
Predominantly in emerging nations, the inevitability for sanitary and efficient waste disposal systems has increased because of rate of waste generation development and urbanization. The aim of this study is to use an Arduino microcontroller and ultrasonic sensor technology to design, fabricate, and assess a low-cost smart waste bin. A HC-SR04 ultrasonic sensor is utilized in the designed and fabricated smart waste bin system to sense user proximity. A servo motor is then automatically stimulated to open and close the bin lid without necessitating physical contact. In order to certify reproducibility in settings with limited resources, hardware, embedded programming, and construction were all completed using simply accessible and reasonably priced components. The operational dependability, response time, and detection accuracy were used for performance evaluation. The experimental outcomes showed constant system performance, less false activation, and reliable lid actuation within the sensing range calibrated. The smart waste bin's design and fabrication greatly advances waste handling proficiency, user convenience, and hygiene. The study establishes that low-cost embedded automation can enhance sanitation infrastructure and offers a scalable foundation for future smart waste management systems.